Recent progress in the performances of ultrastable quartz resonators and oscillators - Salzenstein, Patrice (International journal for simulation and multidisciplinary design optimization, 2016)
Stressed compensated (SC) cut led recently to the best frequency stability ever obtained with a quartz oscillator, 2.5 × 10−14 for the flicker frequency modulation (FFM) floor. This result is confirmed in this paper with a 3.2 × 10−14 ± 1.1 × 10−14. The quartz resonator is integrated in a 5 MHz enhanced aging box double oven controlled oscillator. After reminding a bit of history, this paper describes how the first significant development in terms of ultra-stable quartz state-of-the-art oscillators was performed in the last 20 years, how the resonators were chosen, and main information about the development of adequate electronics and how to mechanically and thermally stabilized such an ultra-stable oscillator. We also present how to characterize the expected performances, and hot topics in quartz based oscillators.